Mount Fuji : icon of Japan - Earhart, H. Byron (Columbia, S.C. : University of South Carolina Press, 2011)
"A survey of the symbolism--religious, aesthetic, and cultural--of Japan's Mount Fuji."--Publisher's description.
Fuji as the Emblem of Peace16 The Future of an Icon; Stereotype and Commercial Logo, Erotica and Exotica; Secular Image and Patriotic Mantra; Epilogue: Descent from the Mountain; Appendix: Sino-Japanese Characters; Notes; Bibliography; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Fuji, Mount (Japan); Mountain worship -- Japan -- Fuji, Mount; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Comparative Religion; Mountain worship; Japan -- Mount Fuji; RELIGION / Comparative Religion; Electronic books